2018
DOI: 10.3390/en11030640
|View full text |Cite
|
Sign up to set email alerts
|

An Agent-Based Model for Zip-Code Level Diffusion of Electric Vehicles and Electricity Consumption in New York City

Abstract: Current power grids in many countries are not fully prepared for high electric vehicle (EV) penetration, and there is evidence that the construction of additional grid capacity is constantly outpaced by EV diffusion. If this situation continues, then it will compromise grid reliability and cause problems such as system overload, voltage and frequency fluctuations, and power losses. This is especially true for densely populated areas where the grid capacity is already strained with existing old infrastructure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…A previous report revealed that during the pre-Covid-19 period, petroleum diesel was sold for USD 3.24 per gallon, while biodiesel cost USD 3.55 [ 69 , 70 ]. Interestingly, a study conducted an evaluation that compared the cost of producing biodiesel with that of petroleum-based biodiesel and concluded that the production of biodiesel might be estimated as USD 2.29 kg −1 .…”
Section: Challenges and Prospectsmentioning
confidence: 99%
“…A previous report revealed that during the pre-Covid-19 period, petroleum diesel was sold for USD 3.24 per gallon, while biodiesel cost USD 3.55 [ 69 , 70 ]. Interestingly, a study conducted an evaluation that compared the cost of producing biodiesel with that of petroleum-based biodiesel and concluded that the production of biodiesel might be estimated as USD 2.29 kg −1 .…”
Section: Challenges and Prospectsmentioning
confidence: 99%
“…The variation in the gasoline price when considering carbon tax T car (t) is given by Equation (13). It is worth mentioning that, if the carbon tax policy is not applied, P g (t) remains constant until 2050.…”
Section: Pb I (T) =mentioning
confidence: 99%
“…One way to evaluate the impact of public policies in the insertion of some specific technology is through building long term scenarios for the sector. For the transportation sector specifically, the main modeling techniques in the literature, to project the insertion of EVs, are agent-based models, consumer choice models, and diffusion and time-series models [9][10][11][12][13]. Among them, diffusion models are the most appropriate to include the impact of public policies in their analysis, with emphasis on the Bass model (BM), which predicts the speed with which the potential market for a specific technology is reached based on two parameters: innovation and imitation [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, the adoption element of the model includes only private vehicle ‘cash’ purchases whereas some 59% of new car purchases are made by fleet buyers in the UK ( DVLA, 2019 ); only two models of EV are included and no long-distance trips are simulated, thus, users do not experience range anxiety. Ahkamiraad and Wang ( Ahkamiraad and Wang, 2018 ) have presented an agent-based EV adoption model that aims to simulate adoption at zip-code level in New York. Each zip-code is an agent with differing adoption rates based on its population characteristics and communication also occurs between neighboring areas.…”
Section: Introductionmentioning
confidence: 99%